What Dubbers of Children’s Television Programmes Can Learn from Translators of Children’s Books? - O’Connell, Eithne (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractTechnical difficulties associated with dubbing, together with the collaborative nature of the dubbing process, explain why traditionally the linguistic challenges of dubbing translation for specific audiences such as children have not been studied very closely. As new developments in sound recording improve the technical quality of dubbing, it is time for the remaining textual translation issues to be addressed in more detail. Due to the many common characteristics of different text types aimed at children, dubbers of children’s audiovisual material can learn a considerable amount from the translators of other texts, such as books and comics aimed at children, about the particular challenges posed by this target audience.